Counseling Service Management for Students Caracter Building in Facing The World of Work (Case Study in State Polytechnic of Balikpapan) - Patria Rahmawaty (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2017)
Counseling is one of educational services for the provision of guidance and counseling for students to form the character that ready to work. The purpose of research is to determine the strategy, forms of cooperation, programs used, the results that obtained and an inhibiting and supporting factors of guidance and counseling services. This research used a qualitative approach with case study method, and the method of data collection using observation, interviews and documentation study. The findings of this research include strategies used in guidance and counseling services that incorporate the budget in budget implementation checklists, discussion with the director, research and comparative studies, guidance personnel must be expert in their section. The form of cooperation involves internal and external institutions. The program that used is service of individual counseling, character building and ethics of the profession. The result is students get an overview of the world of work so that many graduates are absorbed by the world of work. Supporting factors that support director, character building materials, and professional ethics, while the inhibiting factor is funds, counselor manpower which less competent, lack of material resources about counseling. The inference is the implementation of guidance counseling at the State Polytechnic of Balikpapan less than the maximum. The recommendations is the head of counseling must be competent, support from the director of real programs, socialization the importance of guidance and counseling for students.